Satisfaction of the patient’s family member in the Intensive Care Unit of the Hospital Nacional Dos de Mayo, 2018 - Canchero-Ramirez, Andrea (2019)
Introduction. The intensive care unit is an area dedicated to care and treatment to save and preserve life. Objective. Determine the satisfaction of the patient’s family member in the intensive care unit. Methods. Non-experimental cross-sectional design study. The sample consisted of the patient’s family member hospitalized in the Intensive Care Unit of the National Hospital Dos de Mayo. The instrument was used The Patient Satisfaction Questionnaire Short Form designed by Marshall GN and Hayds RD. Results. 127 relatives were interviewed; 54% of the patients corresponded to the male gender, 87,4% had Comprehensive Health Insurance and 92,1% entered the unit for the first time. The equipment for the attention obtained favorable score, the personalized attention was unfavorable. The interpersonal form dimension obtained 60,5% satisfaction and the general satisfaction dimension 79,9%. Conclusions. All dimensions exceeded 60% satisfaction and the total score corresponded to 70,5% satisfaction.